Spring Ozone's Connection to South Africa's Temperature and Rainfall - Manatsa, Desmond; Mukwada, Geoffrey (Frontiers in Earth Science, 2019)
The Brewer–Dobson circulation (BDC), whose dynamic activity is enhanced from winter to spring, transports stratospheric ozone from the tropical source regions to higher latitudes. But it is the BDC’s shallow branch which transfers lower stratospheric ozone (LSO) from the tropics to the subtropics. Hence the accumulation of ozone in the subtropics is at its maximum at the end of spring (October) in the Southern Hemisphere (SH). Here we use observation and observation constrained reanalysis data to investigate the extent to which the interannual variability of this end of spring accumulated LSO is able to impact on the maximum surface air temperature (SATmax) and precipitation of South Africa. This is achieved through contrasting years of high positive and negative October ozone anomalies for the extreme BDC activity, referred to as weak (wBDC) and strong (sBDC) respectively. It is found that the w(s)BDC event composites coincide with significant negative (positive) SATmax anomalies and positive (negative) rainfall over South Africa. We suggest that the wBDC’s related lower stratospheric ozone (LSO) surpluses trap the UVB meant to heat the troposphere and surface. This induces the observed negative middle to upper tropospheric air temperatures and geopotential heights resulting in cyclonic circulation anomalies that enhances rainfall and suppresses SATmax. The opposite is true for the sBDC composites where ultimately the elevated geopotential heights result in middle to upper anticyclonic tropospheric anomalies that are accompanied by rainfall deficits and increased SATmax.